Intercalation pseudocapacitance of FeVO4·nH2O nanowires anode for high-energy and high-power sodium-ion capacitor. (July 2020) - Dong, Jun; He, Yi; Jiang, Yalong; Tan, Shuangshuang; Wei, Qiulong; Xiong, Fangyu; Chu, Zhaolong; An, Qinyou; Mai, Liqiang
Abstract: Sodium-ion capacitors (SICs) can effectively deliver both high energy and power density, which are appropriate for high-rate demanding applications at low-cost. At present, the most developed SICs utilize electric double-layer capacitance (EDLC)-type cathode and battery-type anode, but their capacity is very limited and assembly technique is complex with an inevitable pre-sodiation process. Herein, through systematically comparing the lithium-ion and sodium-ion storage behaviors of FeVO4 ·0.6H2 O nanowires anode, the sodium-ion intercalation mechanism is deeply understood. The FeVO4 ·0.6H2 O anode presents pseudocapacitive sodium-ion intercalation behavior, over 93% of total capacity from capacitive contribution, identified by kinetics analysis, operando XRD and ex-situ TEM characterizations. The FeVO4 ·0.6H2 O anode displays high specific capacity, high initial coulombic efficiency, remarkable rate capability and cycling stability for sodium-ion intercalation. Benefiting from the high-performance pseudocapacitive FeVO4 ·0.6H2 O anode, it is coupled with Na-rich high-rate battery-type cathode (Na3 (VO)2 (PO4 )2 F/rGO) to construct a novel non-aqueous SIC without any additional pre-sodiation process. The assembled SIC delivers a maximum energy density up to 88 Wh kg −1 (at 95 W kg −1 ) and a high power density of 7.9 kW kg −1 (with 35 Wh kg −1 ), and superior cycling stability (5000 cycles). The anode and cathode operate under very safe potential range, respectively, enabling the high safety of SIC even at rapid rates. Our work presents the significant advantages of pseudocapacitive sodium-ion intercalation anode for obtaining both high energy and high power sodium storage devices. Graphical abstract: The FeVO4 ·0.6H2 O nanowires anode displays intercalation pseudocapacitance, which is applied to assemble a new prototype of sodium-ion capacitor (SIC) without complex and unsafe presodiation process. The SIC delivers high-energy and high-power density, which is beneficial to promote the development of the next-generation high performance SICs. Image 1 Highlights: FeVO4 ·0.6H2 O nanowires anode presents Na + intercalation pseudocapacitance behavior. FeVO4 ·0.6H2 O nanowires anode delivers high-rate capability for sodium-ion storage. The assembled sodium-ion capacitor delivers both high energy and power density, and long-term cycling stability.